Autoantibody profiles in systemic sclerosis; a comparison of diagnostic tests. (3rd April 2021) - Alkema, Wynand; Koenen, Hans; Kersten, Brigit E.; Kaffa, Charlotte; Dinnissen, Jacqueline W. B.; Damoiseaux, Jan G. M. C.; Joosten, Irma; Driessen-Diks, Sophie; van der Molen, Renate G.; Vonk, Madelon C.; Smeets, Ruben L.
Abstract: Objectives: Autoimmune antibody profiling plays a prominent role in both classification and prognosis of systemic sclerosis (SSc). In the last years novel autoantibodies have been discovered and have become available in diagnostic assays. However, standardization in autoimmune serology is lacking, which may have a negative impact on the added value of autoantibodies in diagnosis and prognosis of SSc. In this paper we describe the comparison of commercially available diagnostic assays for the detection of SSc-associated autoantibodies and explored the coexistence of multiple SSc-associated autoantibodies within patients. Methods: Serum samples of 347 patients from the Nijmegen Systemic Sclerosis Cohort were included in this study. All patients fulfilled the ACR/EULAR 2013 classification criteria for SSc and were classified as DcSSc or LcSSc according to the Leroy and Medsger criteria. All samples were evaluated on standard laboratory diagnostic tests for detection of SSc-specific autoantibodies CENPA and CENPB (ACA), Scl-70 (ATA), RNA Polymerase III (rp11/155) (ARA), and SSc-associated autoantibodies Fibrillarin, Th-To, PM-scl75, PM-Scl100, RNP68/A/C, Ku, NOR90, and PDGFR from suppliers EUROIMMUN, D-tek and Thermo Fisher Scientific. Results: We found that 79% of the patients was positive for one or more of the SSc autoantibodies. Overall, a high agreement was observed between the diagnostic methods for the SSC-specific autoantibodies listed in the ACR/EULAR criteria (ATA, ACA, and ARA) (Cohen's kappa 0.53–0.97). However, a lower agreement was found for SSc-associated autoantibodies PM-Scl, and Ku, as well as for the SSc-specific autoantibodies fibrillarin and Th-To. Furthermore, the data revealed that the presence of ATA, ARA and ACA is predominantly mutually exclusive, with only a fraction of the patients testing positive for both ATA and ARA. Conclusion: Our data showed high concordance of prevalent SSc-specific autoantibodies between different diagnostic assays. Further standardisation for low prevalent SSc-specific and SSc-associated autoantibodies is needed.